Influence of the Melissa officinalis Leaf Extract on Long-Term Memory in Scopolamine Animal Model with Assessment of Mechanism of Action. (28th April 2016) - Ozarowski, Marcin; Mikolajczak, Przemyslaw L.; Piasecka, Anna; Kachlicki, Piotr; Kujawski, Radoslaw; Bogacz, Anna; Bartkowiak-Wieczorek, Joanna; Szulc, Michal; Kaminska, Ewa; Kujawska, Malgorzata; Jodynis-Liebert, Jadwiga; Gryszczynska, Agnieszka; et al.
Abstract : Melissa officinalis ( MO, English: lemon balm, Lamiaceae), one of the oldest and still most popular aromatic medicinal plants, is used in phytomedicine for the prevention and treatment of nervous disturbances. The aim of our study was to assess the effect of subchronic (28-fold) administration of a 50% ethanol extract of MO leaves (200 mg/kg, p.o.) compared with rosmarinic acid (RA, 10 mg/kg, p.o.) and huperzine A (HU, 0.5 mg/kg, p.o.) on behavioral and cognitive responses in scopolamine-induced rats. The results were linked with acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), and beta-secretase (BACE-1) mRNA levels and AChE and BuChE activities in the hippocampus and frontal cortex of rats. In our study, MO and HU, but not RA, showed an improvement in long-term memory. The results were in line with mRNA levels, since MO produced a decrease of AChE mRNA level by 52% in the cortex and caused a strong significant inhibition of BACE1 mRNA transcription (64% in the frontal cortex; 50% in the hippocampus). However, the extract produced only an insignificant inhibition of AChE activity in the frontal cortex. The mechanisms of MO action are probably more complicated, since its role as a modulator of beta-secretase activity should be taken into consideration.